Prevalence Study of Intestinal Parasites in Stray Cats in USMKK, Health Campus - Mohamad, Ahmad Munir (Universiti Sains Malaysia, 2006)
This dissertation is written for the final year project. It is a study of a prevalence of intestinal parasites in stray cats in USMKK Health Campus. A total of 25 stray cats had been caught within 3 months. 5 stray cats were caught from Desasiswa Nurani, 10 from Desasiswa Murni, 5 from School of Medical Sciences, 2 from School of Health Sciences and 3 from around the USM hospital area. From the total of all 25 stray cats, 9 types of intestinal parasites had been identified from their stool samples by using saline wet mount preparation and Lugol's iodine wet mount preparation. The overall prevalence of intestinal parasites infection was 1000/0 out of the 25 cats which involved in this study. Those parasites are Taenia taeniaeformis, Hookworms, Trichuris spp., Diphyllobothrium latum, Toxocara cati, Toxoplasma gondii, Giardia lamblia, and Isospora felis. The highest prevalence among those intestinal parasites is Toxocara cati with the prevalence of 720/0. The prevalence of Ancylostoma spp. is the second highest and that is 48%. Taenia taeniaeformis and Trichuris spp. have the same prevalence of 40%. The prevalence of Toxoplasma gondii and Isospora felis are both 32%) among the 25 stray cats. Then Diphyllobothrium latum and Giardia lambia, both had a prevalence of 28%). The prevalence of these intestinal parasites inside the stool samples of stray cats in USMKK Health Campus should be given a quick and effective response from the authorities of this campus so that public health wellness in this campus is left unharmed.